The impact of teaching from home during the covid-19 pandemic on the student evaluations of female academics. - Tangalakis, Kathy; Kelly, Kate; KonYu, Natalie; Hall, Dianne (Journal of University Teaching & Learning Practice v.19 n.1 p.160-175 https://doi.org/10.53761/1.19.1.10, 2022)
Student Evaluation of Teaching (SET) results play an important role in academic staff performance evaluation, but also in promotion processes. However, there is much evidence to suggest that the SET used in most universities across the Anglosphere has traditionally penalised female academics. As universities manage the recovery phase of the COVID-19 pandemic, they will also need to take into account the effect of remote teaching on the validity of student evaluation data. Given SET are critical to promotion success, it is important to then understand the gendered effect of remote teaching on student evaluations. We aimed to evaluate how intrusions of family life, academics' home environment and competence with remote teaching technology of female academics were viewed by students and if there were noticeable differences in SET data. We analysed 22,485 SET data over 2019 (pre-COVID, face-to-face teaching) and 2020 (COVID-lockdowns, remote teaching) for female and male academics, matched with student gender, in the multidisciplinary First Year College at Victoria University, Melbourne Australia. Our results showed that there were no differences in the score ratings for teacher gender. However, the qualitative data showed that whilst overall there were overwhelmingly positive comments for both male and female teachers, there was an increase in the negative comments on teaching style by male students toward their female teachers during remote teaching and overall more comments relating to attitude. We speculate that this would have a negative impact on the confidence of teaching-intensive female academics hindering their leadership aspirations and career progression in academia. [Author abstract]